MARKETING STRATEGIES FOR IMPROVING THE EXPORT POTENTIAL OF UZBEKISTAN (BY THE EXAMPLE OF TEXTILES - BAZAROVA FAYYOZA; HAKBERDIYEVA NOZIMA (International Journal of Innovations in Engineering Research and Technology, 2021)
Thisarticle discusses the state of light industry of the Republic ofUzbekistan, the process of development of the industry, as well as its role in ensuring economicgrowth.The prospects of further development of light industry in the Republic of Uzbekistan are analyzed, namely: increasing the export potential of the industry,equipping industry enterprises with modern equipment, usingnew technologies, further increasing the volume of finished products, including high-quality consumer products, increasing the depth of processing of cotton fiber,producing environmentally friendly pure textile product